Can performance‐based financing help reaching the poor with maternal and child health services? The experience of rural Rwanda. (29th June 2015) - Lannes, Laurence; Meessen, Bruno; Soucat, Agnes; Basinga, Paulin
Summary: More than 20 countries in Africa are scaling up performance‐based financing (PBF), but its impact on equity in access to health services remains to be documented. This paper draws on evidence from Rwanda to examine the capacity of PBF to ensure equal access to key health interventions especially in rural areas where most of the poor live. Specifically, it focuses on maternal and child health services, distinguishing two wealth groups, and uses data from a rigorous impact evaluation. Difference‐in‐difference technique is used, and different model specifications are tested: control for unobserved heterogeneity and common random error using linear probability model, seemingly unrelated regression equations, and clustering and fixed effects. Results suggest that in Rwanda, PBF improved efficiency rather than equity for most health services. We find that PBF achieved efficiency gains by improving access to health services for those easier to reach, generally the relatively more affluent. It turns out to be less effective in reaching the poorest. Our results illustrate the advantages of rigorous randomized impact evaluation data as results published earlier using a nationally representative survey (Demographic and Health Survey) were not able to capture the pro‐rich nature of the PBF scheme in Rwanda. Our paper advocates for building mechanisms targeting the vulnerable groups in PBF strategies. It also highlights the need to understand the impact of PBF together with the specific development of health insurance coverage and the organization of the health system.